Analisis Pembinaan Karakter: Membangun Transformasi Insan Kamil Menurut Pemikiran Imam Al-Ghazali - Ariani, Rina; Ritonga, Mahyudin (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
Character development in Islamic education is an integral part of shaping a generation with strong faith and high morals. The thoughts of Imam Al-Ghazali, as one of the leading figures in the intellectual tradition of Islam, provide a strong foundation for the development of the concept of "Insan Kamil" or the perfect human. This article aims to analyze the patterns of character development according to Imam Al-Ghazali's thoughts, focusing on efforts towards the transformation of Insan Kamil within the context of Islamic education. The research method employed is a descriptive-analytical approach to examine various works and concepts proposed by Imam Al-Ghazali regarding character development and the concept of Insan Kamil. Analysis is conducted on Al-Ghazali's classical texts and modern interpretations to understand their relevance and applicability in today's educational context. Findings from the study indicate that the concept of character development according to Imam Al-Ghazali provides a robust foundation for holistic and sustainable Islamic education. Principles taught by Al-Ghazali, such as emphasis on noble ethics, simplicity, and honesty, can effectively be integrated to shape individuals who are not only intellectually capable but also morally upright in everyday life.